Treatment of Fixed Assets Against IFRS - Thesalonika Djumaifin; Felix Chandra Pranoto; Hwianus Hwianus (Akuntansi, 2024)
Adjustment of the treatment of fixed assets to International Financial Reporting Standards (IFRS) has a significant impact on accounting practices throughout the world. This article discusses the treatment of fixed assets in IFRS based on an entity's or company's compliance with international standards which are used as a guide in financial reporting. This research aims to compile a Meta-Analysis of five leading international journals on the Treatment of Fixed Assets Based on IFRS. The meta-analysis method used in this article is to analyze and compile findings from 5 international journals which have discussed the treatment of fixed assets based on IFRS in various countries. The objects of this research are India, Russia, China, Brazil and Romania. These results produce information that from these results it is known that IFRS Principles and Theory show that there are similarities and differences in the adoption and application of IFRS, especially in the context of fixed asset recognition and valuation in the public sector in each country. Although IFRS provides comprehensive financial reporting standards, adjustments and interpretations are still required to ensure its effective application in the unique public sector context.